Pelatihan Pengelolaan Keuangan Digital Bagi UMKM sebagai Upaya Meningkatkan Daya Saing di Pasar Global di desa Cibatu Cikarang Selatan - Rumsina Lubis; Etty Zuliawati Zed; Sumiati Sumiati; Yemima Filadelvia Sinaga (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the effectiveness of digital financial management training for Micro, Small, and Medium Enterprises (MSMEs) in Cibatu Village, South Cikarang. In the digital era, the ability to manage finances effectively is key for MSMEs to increase competitiveness in the global market. The method we used in this research is a quantitative approach with an experimental design, where participants were divided into a training group and a control group The results of the study showed a significant increase in digital financial management knowledge and skills after the training. In addition, participants also reported increased confidence in using technology for their business. The findings suggest that this training can be an effective strategy to empower MSMEs, encourage them to adapt to market changes, and expand their business reach at the global level. Recommendations for future research extend to the development of a more comprehensive training program as well as a long-term assessment of the impact of this training on MSME growth